Key Factors Affecting E-Health Adoption among Young Adults in Malaysia - Haneffa Muchlis Gazali; Tamrin Amboala (Global Journals, 2021)
Introduction: The technological advancement has changed the way people live their life such as communication, travel, learning and shopping. The health sector was also influenced by the technological changes. Objectives: The objective of this study is to develop a model on consumer adoption on electronic health (e-health) in Malaysia. Methods: Extending the Technology Acceptance Model (TAM) with Personal Innovativeness in IT and Social Influence. This paper presents the conceptual foundation on the adoption of e-health among young adults in Malaysia. Results: These initial results suggest a link between TAM, PI and SI towards the adoption of e-health. These findings may help us to better understand the adoption behaviour among young adults towards the application of e-health. Conclusion: This study offers a fresh perspective on the health adoption among young adults in Malaysia. The present study adds to the growing body of literature on e-health adoption in Malaysia. This study is relevant to both practitioners and policy-makers. Due to the conceptual constrain, this paper cannot provide a comprehensive evidence on the e-health adoption from the empirical point of view. Further studies on the current topic are therefore recommended to develop a full picture of e-health adoption which take these variables into account.